The Influence of Profitability, Liquidity and Sales Volume on Financial Distress in Retail Companies Listed on the IDX - Masruroh; Purnamawati, Anni Muslimah (Faculty of Islamic Economics and Business, Madura Islamic State University, 2025)
This study aims to analyze the influence of profitability, liquidity, and sales volume on financial distress in retail companies listed on the Indonesia Stock Exchange (IDX). The primary focus of this study is to identify the financial variables that play the most significant role in determining a company's vulnerability to financial distress, particularly amidst changing consumer behavior, which now favors online transaction. This study uses a quantitative approach with multiple linear regression analysis. Secondary data were obtained from the annual financial reports of retail companies listed on the Indonesia Stock Exchange. Data testing included classical assumption tests (normality, autocorrelation, heteroscedasticity, and multicollinearity) as well as partial tests (t-test) and simultaneous tests (F-test). The regression model was declared feasible because it met all classical assumptions. The results of the study indicate that profitability has a negative and significant effect on financial distress. Conversely, liquidity and sales volume do not significantly influence financial distress. However, simultaneously, profitability, liquidity, and sales volume do not significantly influence financial distress. Practically, the results of this study emphasize the importance of profitability as a key indicator in assessing bankruptcy risk in the retail sector. Management needs to focus strategies on improving asset efficiency and controlling costs to strengthen financial performance. For investors and creditors, profitability ratios can serve as a primary benchmark in assessing the financial health of retail companies. Meanwhile, the insignificant results for liquidity and sales volume variables suggest that classic financial ratios need to be combined with operational and non-financial indicators such as digital innovation and supply chain management to comprehensively understand distress risk. The lack of involvement of sales volume variables in previous studies is one of the limitations that needs to be improved in research related to financial distress.